Sodium-glucose cotransporter 2 inhibitors and the risk of diabetic ketoacidosis: from pathophysiology to clinical practice - Patoulias, Dimitrios; Avranas, Konstantinos (Cardiovascular & hematological disorders, drug targets, 2018)
Background: SGLT-2 inhibitors are a novel class of antidiabetic drugs, recently - approved for the treatment of patients with T2DM. Their cardioprotective an...
Gesehen am 18.02.2020